Behaviour of Factors II, VII, IX and X in Bleeding Complications During Long-Term Treatment with Coumarin - Loeliger, E. A; Hensen, A; Mattern, Mieke J.; Hemker, H. C (Thrombosis and Haemostasis, 1963)
In 20 patients suffering from bleeding complications during long-term treatment with phenprocoumon, the depression of the activity of Factors II, VII, IX and X, on the average, was found to be stronger than in so-called adequately treated patients, whereas no statistically significant differences could be demonstrated between the average activity of the 4 factors. The individual variations between the 4 factors were higher than those found in normal individuals and adequately treated patients.Thrombotest activity appeared to be considerably lower than the average factor activity. This discrepancy is mainly caused by the action of the recently discovered circulating anticoagulant occurring in coumarin-treated or vitamin K-deficient patients.